Fabrication of Electrospun Chitosan/Nylon 6 Nanofibrous Membrane toward Metal Ions Removal and Antibacterial Effect - Akram R. Jabur; Laith K. Abbas; Saja A. Moosa (Advances in Materials Science and Engineering)
Nylon 6/Chitosan membranes were fabricated by electrospinning onto a Millipore glass fiber filter to produce nanofibrous filter. Scanning electron microscopy (SEM) and water contact angle (WCA) were done to characterize the produced filter. Filter removal capability (adsorption) for metal ions was investigated for lead nitrate (Pb(NO3)2) and sodium chloride (NaCl). The antibacterial effect of the Nylon 6/Chitosan was investigated for Escherichia coli. Removal optimum values for Pb(NO3)2 and NaCl reached 87% and 75%, respectively. This research demonstrated that Nylon 6/Chitosan nanofibrous membrane has an enormous applicable potential removal for metal ions from aqueous solutions, antibacterial activity reaching 96%, and reasonable inhibition zone against Escherichia coli (E. coli).